Upper gastrointestinal bleeding of non-variceal origin: ROUND TABLE - Alonso, Oscar; Borgno, Laura; Fenocchi, Eduardo; Misa, Ricardo; Valiñas, Roberto; Olascuaga, Carlos (Cirugía del Uruguay, 1999)
Digestive hemorrhage is the most frequent complication of gastroduodenal ulcer disease with a mortality ranging between 8% and 15% depending on topography and patient's general conditions. The authors present its etiopathogenesis as we/1 as the most relevant endoscopic features, and its indication for diagnosis or primary or definitive treatment, taking Forrest's classification as one of the most important parameters for evaluation of hemorrhagic recidive risk